Crusted (Norwegian) Scabies and HTLV-1 Infection Association: A Case Report - Times de Carvalho, Bernardo; Arcoverde Perrier, Arthur; Maria Mirelle de Macedo e Silva, Patricia; Roberto Cabral da Silva, Joao (International Journal of Innovative Research in Medical Science, 2021)
Crusted scabies, formerly known as Norwegian scabies is as uncommon presentation of scabies that may occur in the in association with an immunosuppressive status. The article aims to present a case report in which a male patient with HTLV-1 carrier status admitted for investigation of eczematous and crusted chronic skin lesions and submitted to a dermatologic evaluation and a skin biopsy considering the hypothesis of a cutaneous form of lymphoma associated with HTLV-1 infection had the diagnosis of Crusted scabies instead. There is data regarding de association of crusted scabies and Human T-lymphotropic virus type 1 (HTLV-1) chronic infection. Therefore, this important diagnosis should always be accessed specially in HTLV-1 endemic regions.